Redox Properties of Human Erythrocytes Are Adapted for Vitamin C Recycling - Eigenschink, Michael; Savran, Danylo; Zitterer, Christoph P.; Granitzer, Sebastian; Fritz, Magdalena; Baron, David M.; Müllner, Ernst W.; Salzer, Ulrich (Frontiers in Physiology, 2021)
Ascorbic acid (AA; or vitamin C) is an important physiological antioxidant and radical scavenger. Some mammalian species, including homo sapiens, have lost the ability to synthetize AA and depend on its nutritional uptake. Erythrocytes from AA-auxotroph mammals express high amounts of the glucose transporter GLUT1. This isoform enables rapid uptake of glucose as well as dehydroascorbate (DHA), the fully oxidized form of AA. Here, we explored the effects of DHA uptake on the redox metabolism of human erythrocytes. DHA uptake enhanced plasma membrane electron (PMET) activity. This process is mediated by DCytb, a membrane bound cytochrome catalyzing extracellular reduction of Fe3+ and ascorbyl free radical (AFR), the first oxidized form of AA. DHA uptake also decreased cellular radical oxygen species (ROS) levels. Both effects were massively enhanced in the presence of physiological glucose concentrations. Reduction of DHA to AA largely depleted intracellular glutathione (GSH) and induced the efflux of its oxidized form, GSSG. GSSG efflux could be inhibited by MK-571 (IC50 = 5 µM), indicating involvement of multidrug resistance associated protein (MRP1/4). DHA-dependent GSH depletion and GSSG efflux were completely rescued in the presence of 5 mM glucose and, partially, by 2-deoxy-glucose (2-DG), respectively. These findings indicate that human erythrocytes physiologically adapted to recycle AA both intracellularly via GLUT1-mediated DHA uptake and reduction and extracellularly via DCytb-mediated AFR reduction. We discuss the possibility that this improved erythrocyte-mediated AA recycling was a prerequisite for the emergence of AA auxotrophy which independently occurred at least twice during mammalian evolution.